Field-scale fluorescence fingerprinting of biochar-borne dissolved organic carbon. (15th March 2016) - Uchimiya, Minori; Liu, Zhongzhen; Sistani, Karamat
Abstract: Biochar continues to receive worldwide enthusiasm as means of augmenting recalcitrant organic carbon in agricultural soils. Realistic biochar amendment rate (typically less than 1 wt%) in the field scale, and subsequent loss by sizing, rain, and other transport events demand reliable methods to quantify the remaining portions of amended biochar. This study employed fluorescence excitation-emission (EEM) spectrophotometry and parallel factor analysis (PARAFAC) to specifically target pyrogenic dissolved organic carbon (DOC) released by amended biochar during the course of a field trial at Bowling Green, KY experimental site. Toluene/methanol (1:6 v/v) extracts of surface (0–15 cm) soils amended with 21.28 t ha −1 fast pyrolysis biochar afforded PARAFAC fingerprints representing different degrees of aromaticity. Compared to the control without treatments, biochar treatment (with and without poultry manure or chemical fertilizer) increased the relative contribution of PARAFAC fingerprint attributable to labile polyaromatic DOC structures. Poultry manure or chemical fertilizer alone (without biochar) did not influence the amounts of polyaromatic DOC structures. Existence of biochar could be further validated by the changes in %DOC (relative to the total carbon), fixed C content, and UV absorbance (360 nm), whereas FTIR, %O, and sorption of model agrochemical (deisopropylatrazine) did not reflect the presence of biochar in the soil samples. Developed toluene/methanol-based EEM-PARAFAC technique will provide a sensitive, rapid, and cost-competitive method to validate the long-term carbon sequestration by the biochar soil amendment. Highlights: Polyaromatic dissolved organic carbon was extractable by toluene/methanol. Fluorescence EEM/PARAFAC validated the presence of pyrogenic DOC. Biochar amendment augments recalcitrant forms of dissolved and particulate carbon.